Integrasi Sertifikasi Syariah dalam Profesi Notaris: Analisis Hukum Perbandingan, Tantangan, dan Peluang di Negara-Negara Muslim Asia Tenggara. - Anand, Ghansham; Purnamawadita, Baiq Elma; Nugraha, Xavier; Rahmat , Nur Ezan (Syariah: Jurnal Hukum dan Pemikiran, 2024)
Southeast Asia is part of the Asian continent located in Southeastern part of Asia or around Indochina and the islands of the Malay Peninsula. Southeast Asia is home to a largely Muslim demographic, such as Indonesia, Malaysia, Brunei Darussalam, Thailand, and the Philippines. Consequently, countries in Southeast Asia implement Islamic law into their national laws, either whole or partially. The primary sources of Islamic law are the Qur'an and Sunnah. Islamic law is frequently applied in business and banking transactions, requiring deeds or agreements. A notary is an authorised individual entitled to make authentic deeds and other documents as regulated in laws and regulations. In several Southeast Asian countries, notaries have the authority to attest an agreement or document. The making of these deeds and agreements also includes agreements based on Islamic law or Sharia law. Thus, notaries can make deeds and agreements based on Islamic law that is recognized and regulated by their respective national laws. However, in making Sharia deeds, not everyone understands the rules and principles of Islamic law, including notaries. There is a current urgency for the standardization of Sharia deed making. This serves as a crucial tool for achieving legal unification in the creation of Sharia deeds on a cross-border scale.